Rural Economic Development in the 1980s Preparing for the Future. (Distributed by ERIC Clearinghouse, 1987)
Seventeen papers review recent changes in the structure and performance of the rural economy and examine alternative policies to facilitate the adjustment of displaced people and their communities. Some point to economic structural change in the 1980s as the cause of financial stress in rural America, in sharp contrast with the 1970s when growth and economic vitality were the dominant rural themes. Results indicate a rural economy that has shifted from dependence on natural resource-based industries to increasing reliance on manufacturing and low-wage, low-skilled service industries. At the same time, the rural economy has apparently become more closely linked to national and global economies, making it more sensitive to changes in macro policy and global competition. Downturns in industries that are important to rural areas indicate a national rural decline accompanied by underdeveloped human resources. Problems associated with rural policy are viewed at the macro, sectoral, territorial, and human resource levels. The analysis of rural conditions and economic forces at work leads to observations about alternatives for future rural policy: (1) future development policies must allow industries to modernize and become more competitive; (2) rural economic policies that depend on the revival of farming, mining, or energy sectors are unlikely to succeed; and (3) states may be key to promoting collaboration among neighboring rural communities. The document concludes that the choice of national rural development policy is ultimately political, a balancing of interests among groups whose futures are being affected. The various papers in this collection include about 275 references and numerous tables, graphs, and maps. (TES)